Time-series analysis and cyclostratigraphy : examining stratigraphic records of environmental cycles - Weedon, Graham P. (Graham Peter), 1962- (Cambridge University Press, 2003)
Cyclostratigraphy is the study of climatic changes recorded in sediments, ice cores and tree rings. This book explains how to analyse these records, or time-series, without using complex mathematical derivations. An essential reference for researchers, and suitable for senior undergraduate and graduate courses in environmental science, palaeoceanography and geology.